Squamata, Scincidae, Mabuya dorsivittata (Cope, 1862): Distribution extension in Buenos Aires province, Argentina - Williams, Jorge Daniel (2011)
Mabuya dorsivttata is a lizard with a wide distribution in South America. In Buenos Aires province, Argentina, previous voucher records exist only from its northern sector and from Mar del Plata city. In this work, two new records of M. dorsivittata from Buenos Aires province are presented: (1) Azul city (36°46’50” S, 50°51’10” W) and (2) Mar del Tuyú city (37°20’08” S, 59°07’60” W). These new records are located about 175 km from the nearest previous record.